Concrete prepared using tailings sand and preparation method thereof
By adding compound whiskers of calcium titanate whiskers, silicon nitride whiskers and magnesium borate whiskers to the concrete, the problem of the decline in the concrete strength after tailings sand replaced river sand is solved, and high-strength concrete preparation is achieved, which is suitable for high-strength projects.
Patent Information
- Application Number
- CN202411139313.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-08-20
AI Technical Summary
Adding a large amount of tailings sand to concrete can effectively solve the problem of environmental pollution, but it will cause a decrease in the strength of concrete and affect the quality of concrete.
By adding compound whiskers of calcium titanate whiskers, silicon nitride whiskers and magnesium borate whiskers to the concrete, and through the combination of specific proportions, the strength after curing of concrete is significantly improved.
After using tailings sand in concrete to replace conventional river sand, the compressive strength can still reach a high level. It is suitable for various projects with high strength requirements and has a wide application space.
Smart Images

Figure BDA0005000304360000101
Abstract
Description
Technical Field
[0001] The invention relates to the field of concrete, and in particular to concrete prepared by utilizing tailings sand and a preparation method thereof. Background Art
[0002] Tailings sand refers to the waste discharged by a mineral processing plant after grinding the ore and selecting the useful components under specific economic and technical conditions. It is generally a solid mineral waste formed by natural dehydration of the tailings slurry discharged by the mineral processing plant. It is a composite silicate or carbonate mineral material. The accumulation of a large amount of tailings sand will occupy land and cause environmental pollution. In order to digest the tailings sand, it is usually used as filler in concrete, so that a large amount of tailings sand can be reused.
[0003] Although adding a large amount of tailings sand to concrete can effectively solve the problem of environmental pollution, the strength of the concrete produced will decrease after tailings sand is completely used to replace river sand, affecting the quality of the concrete. Therefore, there is still room for improvement. Summary of the invention
[0004] In order to improve the strength of concrete, the present application provides concrete prepared using tailings sand and a preparation method thereof.
[0005] In the first aspect, the present application provides a concrete prepared by using tailings sand, adopting the following technical solution:
[0006] A concrete prepared by using tailings sand, comprising the following components in parts by weight:
[0007] 150-155 parts of water;
[0008] Cement 265-270 parts;
[0009] 40-45 parts of fly ash;
[0010] Tailings sand 750-800 parts;
[0011] Crushed stone 1050-1100 parts;
[0012] Composite whiskers 27-33 parts;
[0013] 4-6 parts of admixture;
[0014] The composite whisker is a compound of calcium titanate whisker, silicon nitride whisker and magnesium borate whisker.
[0015] By adopting the above technical scheme, by adding calcium titanate whiskers, silicon nitride whiskers and magnesium borate whiskers into concrete, and by the cooperation of calcium titanate whiskers, silicon nitride whiskers and magnesium borate whiskers, the strength of concrete after solidification can be significantly improved, so that after tailings sand is used in concrete to completely replace conventional river sand, the compressive strength can still reach a high level, so that it can be better applicable to various projects with high strength requirements and has a wide application space.
[0016] Preferably, the mass ratio of the calcium titanate whisker, the silicon nitride whisker, and the magnesium borate whisker is 9-11:10-12:8-10.
[0017] By adopting the above technical scheme and specifically selecting the mass ratio of calcium titanate whiskers, silicon nitride whiskers and magnesium borate whiskers, the calcium titanate whiskers, silicon nitride whiskers and magnesium borate whiskers can cooperate with each other to better improve the strength of concrete, thereby making the quality of the concrete higher after solidification and better applicable to various high-strength projects.
[0018] Preferably, the admixture is a compound of a water reducing agent and a retarder.
[0019] By adopting the above technical solution and adding a water reducing agent and a retarder, the processing performance and quality of the concrete mixture are improved.
[0020] Preferably, the mass ratio of the water reducer to the retarder is 2-3:2-3.
[0021] By adopting the above technical solution and specifically selecting the mass ratio of the water reducer and the retarder, the processing performance of the concrete mixture can be improved and the processing cost can be reduced.
[0022] Preferably, the water reducer is a polycarboxylate water reducer.
[0023] By adopting the above technical scheme and specifically selecting the polycarboxylate water-reducing agent, the water-reducing effect is better, the dosage is less, it has good water retention performance, the water seepage phenomenon is greatly reduced, and the quality of concrete is better.
[0024] Preferably, the retarder is a compound of sodium gluconate and white sugar.
[0025] By adopting the above technical solution and specifically selecting the compound of sodium gluconate and white sugar, the retarding effect is better, the construction time is extended, and the construction difficulty is reduced.
[0026] Preferably, the mass ratio of the sodium gluconate to white sugar is 1-1.5:1-1.5.
[0027] By adopting the above technical solution and specifically selecting the mass ratio of sodium gluconate and white sugar, the retarding effect is better, the concrete performance is not easily affected, and the quality is higher.
[0028] In a second aspect, the present application provides a method for preparing concrete using tailings sand, using the following technical solution:
[0029] A method for preparing concrete using tailings sand comprises the following steps:
[0030] Step 1), cement, fly ash, tailings sand, crushed stone, composite whisker and admixture are uniformly mixed to obtain a premix;
[0031] Step 2), adding water to the premix and mixing evenly to obtain a concrete mixture;
[0032] Step 3), injecting the concrete mixture into a mold, curing, and demoulding to obtain concrete prepared using tailings sand.
[0033] By adopting the above technical solution, the prepared concrete has higher strength, and tailings sand can be used to completely replace conventional river sand without affecting the performance of concrete. It can not only protect the environment, but also enable the prepared concrete to be better used and have higher economic value.
[0034] In summary, this application has the following beneficial effects:
[0035] 1. Since the present application adds calcium titanate whiskers, silicon nitride whiskers and magnesium borate whiskers to concrete, and the calcium titanate whiskers, silicon nitride whiskers and magnesium borate whiskers cooperate with each other, the strength of the concrete after curing can be significantly improved, so that after the tailings sand is completely replaced by conventional river sand in the concrete, the compressive strength can still reach a high level, so that it can be better applied to various projects with high strength requirements and has a wide application space.
[0036] 2. In the present application, it is preferred to specifically select the mass ratio of calcium titanate whiskers, silicon nitride whiskers, and magnesium borate whiskers so that the calcium titanate whiskers, silicon nitride whiskers, and magnesium borate whiskers cooperate with each other to better improve the strength of concrete, thereby making the quality of the concrete higher after curing and better applicable to various high-strength projects. DETAILED DESCRIPTION
[0037] The present application is further described in detail below with reference to the embodiments.
[0038] Example 1
[0039] A concrete prepared by using tailings sand is prepared from the following components:
[0040] Water, cement, fly ash, tailings sand, crushed stone, composite whisker, admixtures.
[0041] The cement is ordinary Portland cement purchased from Runfeng Cement, standard: PO 42.5R.
[0042] The fly ash was purchased from Lingshou County Yigao Mineral Products Processing Plant, first-grade fly ash.
[0043] The tailings sand was purchased from Ji'an Fuyuan Mineral Sand Development Co., Ltd. with a particle size of 2-3mm.
[0044] The crushed stone was purchased from Lingshou County Rongyu Mineral Products Co., Ltd. with a particle size of 20-30mm.
[0045] The composite whisker is a compound of calcium titanate whisker, silicon nitride whisker and magnesium borate whisker.
[0046] Calcium titanate whiskers were purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.
[0047] Silicon nitride whiskers were purchased from Qinghe County Chaotai Metal Materials Co., Ltd.
[0048] Magnesium borate whiskers were purchased from Hubei Maidehao Chemical Co., Ltd.
[0049] The admixture is a compound of water reducer and retarder.
[0050] The water reducer is a polycarboxylic acid water reducer, which was purchased from Guangzhou Mo Ke Building Materials Technology Co., Ltd.
[0051] The retarder is a compound of sodium gluconate and white sugar.
[0052] Sodium gluconate was purchased from Wujiang Minghao Chemical Co., Ltd.
[0053] White sugar was purchased from Jinan Qinghai Chemical Co., Ltd.
[0054] The preparation method of concrete prepared using tailings sand is as follows:
[0055] Step 1), 265kg cement, 40kg fly ash, 750kg tailings sand, 1050kg crushed stone, 9kg calcium titanate whisker, 10kg silicon nitride whisker, 8kg magnesium borate whisker, 2kg polycarboxylate water reducer, 1kg sodium gluconate, 1kg white sugar are put into a stirring tank, the speed is 60r / min, stirring for 10min, mixing evenly, and obtaining a premix.
[0056] Step 2), add 150kg water to the premix, rotate at 60r / min, stir for 5min, mix evenly, and obtain concrete mixture.
[0057] Step 3), injecting the concrete mixture into the mold, sprinkling water for curing for 3 days, demoulding, sprinkling water for curing for 7 days, and standing for curing for 28 days to obtain concrete prepared by using tailings sand.
[0058] Example 2
[0059] A concrete prepared by using tailings sand is prepared from the following components:
[0060] Water, cement, fly ash, tailings sand, crushed stone, composite whisker, admixtures.
[0061] The cement is ordinary Portland cement purchased from Runfeng Cement, standard: PO 42.5R.
[0062] The fly ash was purchased from Lingshou County Yigao Mineral Products Processing Plant, first-grade fly ash.
[0063] The tailings sand was purchased from Ji'an Fuyuan Mineral Sand Development Co., Ltd. with a particle size of 2-3mm.
[0064] The crushed stone was purchased from Lingshou County Rongyu Mineral Products Co., Ltd. with a particle size of 20-30mm.
[0065] The composite whisker is a compound of calcium titanate whisker, silicon nitride whisker and magnesium borate whisker.
[0066] Calcium titanate whiskers were purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.
[0067] Silicon nitride whiskers were purchased from Qinghe County Chaotai Metal Materials Co., Ltd.
[0068] Magnesium borate whiskers were purchased from Hubei Maidehao Chemical Co., Ltd.
[0069] The admixture is a compound of water reducer and retarder.
[0070] The water reducer is a polycarboxylic acid water reducer, which was purchased from Guangzhou Mo Ke Building Materials Technology Co., Ltd.
[0071] The retarder is a compound of sodium gluconate and white sugar.
[0072] Sodium gluconate was purchased from Wujiang Minghao Chemical Co., Ltd.
[0073] White sugar was purchased from Jinan Qinghai Chemical Co., Ltd.
[0074] The preparation method of concrete prepared using tailings sand is as follows:
[0075] Step 1), 267.5kg cement, 42.5kg fly ash, 775kg tailings sand, 1075kg crushed stone, 10kg calcium titanate whisker, 11kg silicon nitride whisker, 9kg magnesium borate whisker, 2.5kg polycarboxylate water reducer, 1.25kg sodium gluconate, 1.25kg white sugar are put into a stirring tank, the speed is 60r / min, stirring for 10min, mixing evenly, and obtaining a premix.
[0076] Step 2), add 152.5 kg of water to the premix, rotate at 60 r / min, stir for 5 min, mix evenly, and obtain a concrete mixture.
[0077] Step 3), injecting the concrete mixture into the mold, sprinkling water for curing for 3 days, demoulding, sprinkling water for curing for 7 days, and standing for curing for 28 days to obtain concrete prepared by using tailings sand.
[0078] Example 3
[0079] A concrete prepared by using tailings sand is prepared from the following components:
[0080] Water, cement, fly ash, tailings sand, crushed stone, composite whisker, admixtures.
[0081] The cement is ordinary Portland cement purchased from Runfeng Cement, standard: PO 42.5R.
[0082] The fly ash was purchased from Lingshou County Yigao Mineral Products Processing Plant, first-grade fly ash.
[0083] The tailings sand was purchased from Ji'an Fuyuan Mineral Sand Development Co., Ltd. with a particle size of 2-3mm.
[0084] The crushed stone was purchased from Lingshou County Rongyu Mineral Products Co., Ltd. with a particle size of 20-30mm.
[0085] The composite whisker is a compound of calcium titanate whisker, silicon nitride whisker and magnesium borate whisker.
[0086] Calcium titanate whiskers were purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.
[0087] Silicon nitride whiskers were purchased from Qinghe County Chaotai Metal Materials Co., Ltd.
[0088] Magnesium borate whiskers were purchased from Hubei Maidehao Chemical Co., Ltd.
[0089] The admixture is a compound of water reducer and retarder.
[0090] The water reducer is a polycarboxylic acid water reducer, which was purchased from Guangzhou Mo Ke Building Materials Technology Co., Ltd.
[0091] The retarder is a compound of sodium gluconate and white sugar.
[0092] Sodium gluconate was purchased from Wujiang Minghao Chemical Co., Ltd.
[0093] White sugar was purchased from Jinan Qinghai Chemical Co., Ltd.
[0094] The preparation method of concrete prepared using tailings sand is as follows:
[0095] Step 1), 270kg cement, 45kg fly ash, 800kg tailings sand, 1100kg crushed stone, 11kg calcium titanate whisker, 12kg silicon nitride whisker, 10kg magnesium borate whisker, 3kg polycarboxylate water reducer, 1.5kg sodium gluconate, 1.5kg white sugar are put into a stirring tank, the speed is 60r / min, stirring for 10min, mixing evenly, and obtaining a premix.
[0096] Step 2), add 155kg water to the premix, rotate at 60r / min, stir for 5min, mix evenly, and obtain concrete mixture.
[0097] Step 3), injecting the concrete mixture into the mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing for 7 days, and standing for curing for 28 days to obtain concrete prepared by using tailings sand.
[0098] Example 4
[0099] A concrete prepared by using tailings sand is prepared from the following components:
[0100] Water, cement, fly ash, tailings sand, crushed stone, composite whisker, admixtures.
[0101] The cement is ordinary Portland cement purchased from Runfeng Cement, standard: PO 42.5R.
[0102] The fly ash was purchased from Lingshou County Yigao Mineral Products Processing Plant, first-grade fly ash.
[0103] The tailings sand was purchased from Ji'an Fuyuan Mineral Sand Development Co., Ltd. with a particle size of 2-3mm.
[0104] The crushed stone was purchased from Lingshou County Rongyu Mineral Products Co., Ltd. with a particle size of 20-30mm.
[0105] The composite whisker is a compound of calcium titanate whisker, silicon nitride whisker and magnesium borate whisker.
[0106] Calcium titanate whiskers were purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.
[0107] Silicon nitride whiskers were purchased from Qinghe County Chaotai Metal Materials Co., Ltd.
[0108] Magnesium borate whiskers were purchased from Hubei Maidehao Chemical Co., Ltd.
[0109] The admixture is a compound of water reducer and retarder.
[0110] The water reducer is a polycarboxylic acid water reducer, which was purchased from Guangzhou Mo Ke Building Materials Technology Co., Ltd.
[0111] The retarder is a compound of sodium gluconate and white sugar.
[0112] Sodium gluconate was purchased from Wujiang Minghao Chemical Co., Ltd.
[0113] White sugar was purchased from Jinan Qinghai Chemical Co., Ltd.
[0114] The preparation method of concrete prepared using tailings sand is as follows:
[0115] Step 1), 267.5kg cement, 42.5kg fly ash, 775kg tailings sand, 1075kg crushed stone, 13kg calcium titanate whisker, 14kg silicon nitride whisker, 3kg magnesium borate whisker, 2.5kg polycarboxylate water reducer, 1.25kg sodium gluconate, 1.25kg white sugar are put into a stirring tank, the speed is 60r / min, stirring for 10min, mixing evenly, and obtaining a premix.
[0116] Step 2), add 152.5 kg of water to the premix, rotate at 60 r / min, stir for 5 min, mix evenly, and obtain a concrete mixture.
[0117] Step 3), injecting the concrete mixture into the mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing for 7 days, and standing for curing for 28 days to obtain concrete prepared by using tailings sand.
[0118] Example 5
[0119] A concrete prepared by using tailings sand is prepared from the following components:
[0120] Water, cement, fly ash, tailings sand, crushed stone, composite whisker, admixtures.
[0121] The cement is ordinary Portland cement purchased from Runfeng Cement, standard: PO 42.5R.
[0122] The fly ash was purchased from Lingshou County Yigao Mineral Products Processing Plant, first-grade fly ash.
[0123] The tailings sand was purchased from Ji'an Fuyuan Mineral Sand Development Co., Ltd. with a particle size of 2-3mm.
[0124] The crushed stone was purchased from Lingshou County Rongyu Mineral Products Co., Ltd. with a particle size of 20-30mm.
[0125] The composite whisker is a compound of calcium titanate whisker, silicon nitride whisker and magnesium borate whisker.
[0126] Calcium titanate whiskers were purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.
[0127] Silicon nitride whiskers were purchased from Qinghe County Chaotai Metal Materials Co., Ltd.
[0128] Magnesium borate whiskers were purchased from Hubei Maidehao Chemical Co., Ltd.
[0129] The admixture is a compound of water reducer and retarder.
[0130] The water reducer is a polycarboxylic acid water reducer, which was purchased from Guangzhou Mo Ke Building Materials Technology Co., Ltd.
[0131] The retarder is a compound of sodium gluconate and white sugar.
[0132] Sodium gluconate was purchased from Wujiang Minghao Chemical Co., Ltd.
[0133] White sugar was purchased from Jinan Qinghai Chemical Co., Ltd.
[0134] The preparation method of concrete prepared using tailings sand is as follows:
[0135] Step 1), 267.5kg cement, 42.5kg fly ash, 775kg tailings sand, 1075kg crushed stone, 7kg calcium titanate whisker, 8kg silicon nitride whisker, 15kg magnesium borate whisker, 2.5kg polycarboxylate water reducer, 1.25kg sodium gluconate, 1.25kg white sugar are put into a stirring tank, the speed is 60r / min, stirring for 10min, mixing evenly, and obtaining a premix.
[0136] Step 2), add 152.5 kg of water to the premix, rotate at 60 r / min, stir for 5 min, mix evenly, and obtain a concrete mixture.
[0137] Step 3), injecting the concrete mixture into the mold, sprinkling water for curing for 3 days, demoulding, sprinkling water for curing for 7 days, and standing for curing for 28 days to obtain concrete prepared by using tailings sand.
[0138] Comparative Example 1
[0139] A concrete prepared by using tailings sand is prepared from the following components:
[0140] Water, cement, fly ash, tailings sand, crushed stone, composite whisker, admixtures.
[0141] The cement is ordinary Portland cement purchased from Runfeng Cement, standard: PO 42.5R.
[0142] The fly ash was purchased from Lingshou County Yigao Mineral Products Processing Plant, first-grade fly ash.
[0143] The tailings sand was purchased from Ji'an Fuyuan Mineral Sand Development Co., Ltd. with a particle size of 2-3mm.
[0144] The crushed stone was purchased from Lingshou County Rongyu Mineral Products Co., Ltd. with a particle size of 20-30mm.
[0145] The composite whisker is a compound of calcium sulfate whisker, silicon nitride whisker and magnesium borate whisker.
[0146] Calcium sulfate whiskers were purchased from Jinan Sunny Day Chemical Technology Co., Ltd.
[0147] Silicon nitride whiskers were purchased from Qinghe County Chaotai Metal Materials Co., Ltd.
[0148] Magnesium borate whiskers were purchased from Hubei Maidehao Chemical Co., Ltd.
[0149] The admixture is a compound of water reducer and retarder.
[0150] The water reducer is a polycarboxylic acid water reducer, which was purchased from Guangzhou Mo Ke Building Materials Technology Co., Ltd.
[0151] The retarder is a compound of sodium gluconate and white sugar.
[0152] Sodium gluconate was purchased from Wujiang Minghao Chemical Co., Ltd.
[0153] White sugar was purchased from Jinan Qinghai Chemical Co., Ltd.
[0154] The preparation method of concrete prepared using tailings sand is as follows:
[0155] Step 1), 267.5kg cement, 42.5kg fly ash, 775kg tailings sand, 1075kg crushed stone, 10kg calcium sulfate whisker, 11kg silicon nitride whisker, 9kg magnesium borate whisker, 2.5kg polycarboxylate water reducer, 1.25kg sodium gluconate, 1.25kg white sugar are put into a stirred tank at a speed of 60r / min, stirred for 10min, and mixed evenly to obtain a premix.
[0156] Step 2), add 152.5 kg of water to the premix, rotate at 60 r / min, stir for 5 min, mix evenly, and obtain a concrete mixture.
[0157] Step 3), injecting the concrete mixture into the mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing for 7 days, and standing for curing for 28 days to obtain concrete prepared by using tailings sand.
[0158] Comparative Example 2
[0159] A concrete prepared by using tailings sand is prepared from the following components:
[0160] Water, cement, fly ash, tailings sand, crushed stone, composite whisker, admixtures.
[0161] The cement is ordinary Portland cement purchased from Runfeng Cement, standard: PO 42.5R.
[0162] The fly ash was purchased from Lingshou County Yigao Mineral Products Processing Plant, first-grade fly ash.
[0163] The tailings sand was purchased from Ji'an Fuyuan Mineral Sand Development Co., Ltd. with a particle size of 2-3mm.
[0164] The crushed stone was purchased from Lingshou County Rongyu Mineral Products Co., Ltd. with a particle size of 20-30mm.
[0165] The composite whisker is a compound of calcium titanate whisker, calcium carbonate whisker and magnesium borate whisker.
[0166] Calcium titanate whiskers were purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.
[0167] Calcium carbonate whiskers were purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.
[0168] Magnesium borate whiskers were purchased from Hubei Maidehao Chemical Co., Ltd.
[0169] The admixture is a compound of water reducer and retarder.
[0170] The water reducer is a polycarboxylic acid water reducer, which was purchased from Guangzhou Mo Ke Building Materials Technology Co., Ltd.
[0171] The retarder is a compound of sodium gluconate and white sugar.
[0172] Sodium gluconate was purchased from Wujiang Minghao Chemical Co., Ltd.
[0173] White sugar was purchased from Jinan Qinghai Chemical Co., Ltd.
[0174] The preparation method of concrete prepared using tailings sand is as follows:
[0175] Step 1), 267.5kg cement, 42.5kg fly ash, 775kg tailings sand, 1075kg gravel, 10kg calcium titanate whisker, 11kg calcium carbonate whisker, 9kg magnesium borate whisker, 2.5kg polycarboxylate water reducer, 1.25kg sodium gluconate, 1.25kg white sugar are put into a stirring tank, the speed is 60r / min, stirring for 10min, mixing evenly, and obtaining a premix.
[0176] Step 2), add 152.5 kg of water to the premix, rotate at 60 r / min, stir for 5 min, mix evenly, and obtain a concrete mixture.
[0177] Step 3), injecting the concrete mixture into the mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing for 7 days, and standing for curing for 28 days to obtain concrete prepared by using tailings sand.
[0178] Comparative Example 3
[0179] A concrete prepared by using tailings sand is prepared from the following components:
[0180] Water, cement, fly ash, tailings sand, crushed stone, composite whisker, admixtures.
[0181] The cement is ordinary Portland cement purchased from Runfeng Cement, standard: PO 42.5R.
[0182] The fly ash was purchased from Lingshou County Yigao Mineral Products Processing Plant, first-grade fly ash.
[0183] The tailings sand was purchased from Ji'an Fuyuan Mineral Sand Development Co., Ltd. with a particle size of 2-3mm.
[0184] The crushed stone was purchased from Lingshou County Rongyu Mineral Products Co., Ltd. with a particle size of 20-30mm.
[0185] The composite whisker is a compound of calcium titanate whisker, silicon nitride whisker and zirconium oxide whisker.
[0186] Calcium titanate whiskers were purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.
[0187] Silicon nitride whiskers were purchased from Qinghe County Chaotai Metal Materials Co., Ltd.
[0188] Zirconia whiskers were purchased from Ningbo Luofei Nanotechnology Co., Ltd.
[0189] The admixture is a compound of water reducer and retarder.
[0190] The water reducer is a polycarboxylic acid water reducer, which was purchased from Guangzhou Mo Ke Building Materials Technology Co., Ltd.
[0191] The retarder is a compound of sodium gluconate and white sugar.
[0192] Sodium gluconate was purchased from Wujiang Minghao Chemical Co., Ltd.
[0193] White sugar was purchased from Jinan Qinghai Chemical Co., Ltd.
[0194] The preparation method of concrete prepared using tailings sand is as follows:
[0195] Step 1), 267.5kg cement, 42.5kg fly ash, 775kg tailings sand, 1075kg crushed stone, 10kg calcium titanate whisker, 11kg silicon nitride whisker, 9kg zirconium oxide whisker, 2.5kg polycarboxylate water reducer, 1.25kg sodium gluconate, 1.25kg white sugar are put into a stirring tank, the speed is 60r / min, stirring for 10min, mixing evenly, and obtaining a premix.
[0196] Step 2), add 152.5 kg of water to the premix, rotate at 60 r / min, stir for 5 min, mix evenly, and obtain a concrete mixture.
[0197] Step 3), injecting the concrete mixture into the mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing for 7 days, and standing for curing for 28 days to obtain concrete prepared by using tailings sand.
[0198] Comparative Example 4
[0199] A concrete prepared by using tailings sand is prepared from the following components:
[0200] Water, cement, fly ash, tailings sand, crushed stone, composite whisker, admixtures.
[0201] The cement is ordinary Portland cement purchased from Runfeng Cement, standard: PO 42.5R.
[0202] The fly ash was purchased from Lingshou County Yigao Mineral Products Processing Plant, first-grade fly ash.
[0203] The tailings sand was purchased from Ji'an Fuyuan Mineral Sand Development Co., Ltd. with a particle size of 2-3mm.
[0204] The crushed stone was purchased from Lingshou County Rongyu Mineral Products Co., Ltd. with a particle size of 20-30mm.
[0205] The composite whisker is a compound of calcium sulfate whisker, calcium carbonate whisker and zirconium oxide whisker.
[0206] Calcium sulfate whiskers were purchased from Jinan Sunny Day Chemical Technology Co., Ltd.
[0207] Calcium carbonate whiskers were purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.
[0208] Zirconia whiskers were purchased from Ningbo Luofei Nanotechnology Co., Ltd.
[0209] The admixture is a compound of water reducer and retarder.
[0210] The water reducer is a polycarboxylic acid water reducer, which was purchased from Guangzhou Mo Ke Building Materials Technology Co., Ltd.
[0211] The retarder is a compound of sodium gluconate and white sugar.
[0212] Sodium gluconate was purchased from Wujiang Minghao Chemical Co., Ltd.
[0213] White sugar was purchased from Jinan Qinghai Chemical Co., Ltd.
[0214] The preparation method of concrete prepared using tailings sand is as follows:
[0215] Step 1), 267.5kg cement, 42.5kg fly ash, 775kg tailings sand, 1075kg crushed stone, 10kg calcium sulfate whisker, 11kg calcium carbonate whisker, 9kg zirconium oxide whisker, 2.5kg polycarboxylate water reducer, 1.25kg sodium gluconate, 1.25kg white sugar are put into a stirred tank at a speed of 60r / min, stirred for 10min, and mixed evenly to obtain a premix.
[0216] Step 2), add 152.5 kg of water to the premix, rotate at 60 r / min, stir for 5 min, mix evenly, and obtain a concrete mixture.
[0217] Step 3), injecting the concrete mixture into the mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing for 7 days, and standing for curing for 28 days to obtain concrete prepared by using tailings sand.
[0218] Experiment 1
[0219] According to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the 7-day compressive strength, 28-day compressive strength, and 28-day splitting tensile strength of the samples made of the concrete mixture obtained in step 2 in each embodiment and comparative example were tested.
[0220] The experimental data of Experiment 1 are detailed in Table 1.
[0221] Table 1
[0222]
[0223] According to the data comparison between the embodiments and the comparative examples in Table 1, it can be obtained that the compressive strength and splitting tensile strength of the concrete prepared in the embodiments are significantly higher than those in the comparative examples. In the embodiments and the comparative examples, tailings sand is used to completely replace conventional river sand. After the composite whiskers composed of calcium titanate whiskers, silicon nitride whiskers and magnesium borate whiskers in a specific proportion are added to the embodiments, the strength of the concrete after curing is significantly improved. Although the whisker materials are also added to the comparative examples, which also have a certain reinforcement effect, the reinforcement effect is significantly reduced.
[0224] It can be seen that the cooperation between calcium titanate whiskers, silicon nitride whiskers and magnesium borate whiskers can play a very good synergistic role, and the reinforcement effect of concrete using tailings sand to completely replace conventional river sand is better.
[0225] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A concrete prepared using tailings sand, characterized in that: The composition includes the following components in parts by weight: 150-155 parts of water; Cement 265-270 parts; 40-45 parts of fly ash; Tailings sand 750-800 parts; Crushed stone 1050-1100 parts; Composite whiskers 27-33 parts; 4-6 parts of admixture; The composite whisker is a compound of calcium titanate whisker, silicon nitride whisker and magnesium borate whisker; The mass ratio of the calcium titanate whisker, the silicon nitride whisker and the magnesium borate whisker is 9-11:10-12:8-10; The admixture is a compound of a water reducing agent and a retarder.
2. The concrete prepared by using tailings sand according to claim 1, characterized in that: The mass ratio of the water reducer to the retarder is 2-3:2-3.
3. The concrete prepared by using tailings sand according to claim 2, characterized in that: The water reducer is a polycarboxylate water reducer.
4. The concrete prepared by using tailings sand according to claim 2, characterized in that: The retarder is a compound of sodium gluconate and white sugar.
5. The concrete prepared by using tailings sand according to claim 4, characterized in that: The mass ratio of the sodium gluconate to white sugar is 1-1.5:1-1.
5.
6. A method for preparing concrete using tailings sand according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1), cement, fly ash, tailings sand, crushed stone, composite whisker and admixture are uniformly mixed to obtain a premix; Step 2), adding water to the premix and mixing evenly to obtain a concrete mixture; Step 3), injecting the concrete mixture into the mold, curing and demoulding, and obtaining concrete prepared using tailings sand.
Citation Information
Patent Citations
Soundproof wall construction method
CN110847420A
Preparation method of dry-process high-quality tailing machine-made sand and high-strength concrete containing machine-made sand
CN114349380A